From civil strife to peace building : examining private sector involvement in West African reconstruction - Besada, Hany (Studies in international governance., 2009)
From Civil Strife to Peace Building examines peace-building efforts in the fragile West African states of Sierra Leone, Liberia, and Cote d'Ivoire, with a focus on the role of the private sector in leading the reconstruction initiatives. Given that aid and debt relief, the traditional remedies for dependency and underdevelopment, have not been effective, the private sector is increasingly viewed as a major player in the revival of regional economies. Private sector support, however, requires government intervention to improve investment climates, curb corruption, strengthen the security secto.